Обломов - Гончаров Иван Александрович (Школа классики, 1998)
Экземпляры: Селтинская районная библиотека (к/х) (20190814) / Инвентарный номер: 181190 / Цена: / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2=411.2)